PENGARUH SIMPANAN DAN PINJAMAN ANGGOTA TERHADAP SISA HASIL USAHA (SHU) PADA KOPERASI PEGAWAI REPUBLIK INDONESIA (KP-RI) SMP NEGERI KABUPATEN INDRAGIRI HULU - Saputra, R Marwan Indra (Eko dan Bisnis: Riau Economic and Business Review, 2017)
This research was conducted at the Employee Cooperative of the Republic of Indonesia (KP-RI) Indragiri Hulu Regency Public Middle School, which is located at Jl. Cambodia N0. 02 Rengat Regency of Indragiri Hulu. This research is a quantitative study, the data used by the author in this study are secondary data and the research method used is descriptive method. The results of the study there is a significant effect between the Deposits and Member Loans on the Remaining Operating Results (SHU). Deposits partially have a significant effect on the Remaining Operating Results (SHU), Member Loans partially have no significant effect on Remaining Operations (SHU) and from the quantitative calculations obtained it can be seen that there is a strong relationship between the Deposits and Member Loans towards the Remaining Operations (SHU) which has a Correlation value of 0.982